ATZ (3-amino-1,2,4-triazole) injected into the fourth cerebral ventricle influences the Bezold-Jarisch reflex in conscious rats (Clinics, 2010)
OBJECTIVES: Many studies have investigated the importance of oxidative stress on the cardiovascular system. In this study we evaluated the effects of central catalase inhibition on cardiopulmonary reflex in conscious Wistar rats. METHODS: Male Wistar rats were implanted with a stainless steel guide cannula in the fourth cerebral ventricle. The femoral artery and vein were cannulated for mean arterial pressure and heart rate measurement and for drug infusion, respectively. After basal mean arterial pressure and heart rate recordings, the cardiopulmonary reflex was tested with a dose of phenylbiguanide (PBG, 8 μg/kg, bolus). Cardiopulmonary reflex was evaluated before and μl15 minutes after 1.0 μl 3-amino-1,2,4-triazole (ATZ, 0.01g/100μl)0.01 g/100 μl) injection into the fourth cerebral ventricle. Vehicle treatment did not change cardiopulmonary reflex responses. RESULTS: Central ATZ significantly increased hypotensive responses without influencing the bradycardic reflex. CONCLUSION: ATZ injected into the fourth cerebral ventricle increases sympathetic inhibition but does not change the parasympathetic component of the cardiopulmonary reflex in conscious Wistar rats.